A note on Cajetan's theological semantics: in response to Timothy L. Smith's criticisms of Cajetan - Hochschild, Joshua P. (Sapientia, 1999)
In a recent article, Timothy L. Smith has offered an interpretation of the theological method employed by Thomas Aquinas in Surnma Theologiae I1 . Smith offers his interpretation in an attempt to «extricate Thomas from the tangled web of trinitarias criticism and historiography» (136) which has allowed many, under the influence of Régnon and Rahner, to find a theologically suspect «monoperson-alism» in de Deo. While I am sympathetic to Smith's overall project, I believe he fails in his of attempt to identify Thomas de Vio Cajetan as the historical source of the modern hermeneutic mistake. Smith considers in particular Cajetan's commentary on two anides (q. 3 a. 3, and q. 39 a. 4), in which Smith finds evidence that Cajetan «posited an existing divine nature apart from the Persons» (152). According to Smith, «Having defined a concrete, subsistent Deus distinct from the Persons, Cajetan has unwittingly established an absolute divinity that falls into the category of a fourth divine thing. This posited absolute divinity in Cajetan's commentary is the chief source of the `monopersonalism' read into the Surnma» (pp. 149-150). Smith's argument is that Cajetan is led to this mistaken position by misreading Thomas's logical distinctions as metaphysical ones. However, read in the light of the semantic principies that Cajetan assumes, Cajetan's commentary admits to a much different interpretation than Smith gives it. Cajetan, I argue, makes no such metaphysical claim as Smith attributes to him, and it is in fact Smith's interpretation of Cajetan that is guilty of confusing logical and metaphysical distinctions...